Social Comparison in Social Media Among Adolescents: Is it Associated with Lower Life Satisfaction? - Marshella, Reggina Bunga; Samita, Cantya Puspa; Metekohy, Jones Rynes S. (Fakultas Psikologi Universitas YARSI, 2025)
Social media has become the dominant platform for adolescents to interact socially, making them vulnerable to social comparison. This study examines the role of social comparison on life satisfaction in adolescent social media users. This study uses quantitative methods. The sample of this study involved 113 adolescents aged 18-21 who actively use social media, selected using a purposive sampling technique. Data was collected through an online questionnaire using two instruments, namely the Iowa-Netherlands Comparison Orientation Measure (INCOM) to measure social comparison and the Riverside Life Satisfaction Scale (RLSS) to measure life satisfaction. The results of the linear regression analysis indicated that social comparison did not have a significant influence on life satisfaction, with an R2 of .000 and a p-value of .840. This finding indicates that although adolescents might frequently engage in social comparisons on social media, it is not associated with their overall life satisfaction. This study suggests that other factors may play a greater role in determining life satisfaction, so further research is needed to understand the complexities of social comparison in social media use.